Control interno de la cuenta proveedores del almacén de electrodomésticos D´L Malecon de la ciudad de Vinces en el periodo 2022 - Morales Osorio, Yamile Pamela (2023)
Accounts payable to suppliers represent the sum of money that a company owes to its suppliers for the acquisition of merchandise and goods on credit, which are current payments since they must be settled within a minimum period of one year, these accounts payable They are a fundamental part of business economic activity since their study allows us to know the debt capacity and determine the cash flow. Therefore, the objective of this case study was to evaluate, through internal control, the behavior of accounts payable to suppliers and their turnover, in addition to measuring the days that the warehouse pays its financial obligations. The methodological framework consisted of a descriptive study to describe and understand the information collected in the interview with the accountant; it was also based on inductive and deductive methods to understand the study problem. The results of this investigation allow us to conclude that accounts payable are of vital importance in the balance of the D'L MALECON appliance warehouse, likewise the weaknesses found were the inadequate process in the payment term to suppliers, which causes unstable business relationships and a poor credit reputation